Revisiting the Effects of Colonialism on the Development of Customary Laws in Nigeria - Wuraola, Oluwabusayo Temitope; Ojibara, Hameenat Bukola (NIU Journal of Humanities, 2018)
Since the Common Law of England gained the force of law in Nigeria, customary laws have been described as archaic and barbaric. In order to be validly applied as a law, they have to undergo the repugnancy tests set out by the colonial masters. As a result, it is observed that the worth and application of customary laws seem to have diminished. The Common Law of England became applicable alongside statutory legislations and valid customary laws but the customary laws are only valid subject to passing the repugnancy tests set up by the colonial masters. The questions are: Why are customary laws inferior to English laws? Why customary laws are subjected to repugnancy tests for acceptability? This paper seeks to revisit the concept of colonialism and its sting on the development of customary laws and also examine the effects of the repugnancy tests on the development of these laws. Keywords - Customary law, Colonialism, Repugnancy tests, Received english law, Common law, Volksgeist, Nigeria, Inferiority